2019
DOI: 10.1016/j.jhepr.2019.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Promoter hypermethylation of the AE2/SLC4A2 gene in PBC

Abstract: Graphical abstract Highlights• Patients with PBC have higher AE2 CpG methylation in upstream AE2a and/or AE2b2/AE2b1 promoter regions in liver and PBMCs.Background & Aims: Patients with primary biliary cholangitis (PBC) exhibit reduced AE2/SLC4A2 gene expression in the liver and peripheral blood mononuclear cells (PBMCs). AE2 encodes a Cl -/HCO 3 exchanger involved in biliary bicarbonate secretion and intracellular pH regulation. Reduced AE2 expression in PBC may be pathogenic, as Ae2-knockout mice reproduce c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…Recently, Arenas et al discovered there is significant increase in CpG methylation in the promoter regions of AE2α, AE2b1, and AE2b2 in livers of patients with PBC when compared with controls. 118 Consequently, AE2 messenger RNA levels in the liver were also lower in PBC than controls. Since AE2 is involved in bicarbonate secretion, 33 reduction in AE2 expression can negatively affect the bicarbonate umbrella in the biliary tree, leading to bile duct injury.…”
Section: Epigenetics Of Pbcmentioning
confidence: 95%
“…Recently, Arenas et al discovered there is significant increase in CpG methylation in the promoter regions of AE2α, AE2b1, and AE2b2 in livers of patients with PBC when compared with controls. 118 Consequently, AE2 messenger RNA levels in the liver were also lower in PBC than controls. Since AE2 is involved in bicarbonate secretion, 33 reduction in AE2 expression can negatively affect the bicarbonate umbrella in the biliary tree, leading to bile duct injury.…”
Section: Epigenetics Of Pbcmentioning
confidence: 95%
“…(Hisamoto et al, 2016). Since loss of the bicarbonate umbrella, specifically through reduced AE2 expression, is a hallmark of PBC, this data is quite compelling (Arenas et al, 2019;Banales et al, 2012). In human samples, decreased expression of AE2 is correlated with increased bile duct senescence during PBC (Sasaki et al, 2018a), thus identifying that the bicarbonate umbrella may be an important component of PBC progression via increased senescence.…”
Section: Primary Biliary Cholangitismentioning
confidence: 98%
“…Recently, we reported that there is a significant increase in CpG-cytosine methylation affecting selective promoter regions of the AE2 gene both in liver and PBMCs from PBC individuals [ 81 ▪ ]. Moreover, mean methylation rates inversely correlate with mRNA levels [ 81 ▪ ]. Of note, selective CpG-hypermethylation clusters in PBC affected relevant nuclear factor sites/motifs [ 81 ▪ , 82 84 ].…”
Section: Genetic Epigenetic and Environmental Factorsmentioning
confidence: 99%
“…Moreover, mean methylation rates inversely correlate with mRNA levels [ 81 ▪ ]. Of note, selective CpG-hypermethylation clusters in PBC affected relevant nuclear factor sites/motifs [ 81 ▪ , 82 84 ].…”
Section: Genetic Epigenetic and Environmental Factorsmentioning
confidence: 99%